Transformation of chlorine in NaCl-loaded Victorian brown coal during the gasification in steam - Zhang, Shu; Asadullah, M.; Hocking, R.; Lin, J.; Li, Chun-Zhu (2012)
This study is to examine the changes in Cl volatilizations and chemical forms in NaCl-loaded Victorian brown coal during gasification in steam at 800°C using Cl K-edge X-ray absorption near-edge structure (XANES) spectroscopy. The char samples were prepared in a novel one-stage fluidised-bed/fixed-bed quartz reactor at a fast heating rate. The samples were then collected and sealed in an argon-filled bag in order to minimise possible oxidation of char and Cl by air prior to analysis by XANES. Char-steam reactions were found to significantly affect the transformation of Cl, including the possible formation of chlorine-containing organic structures. On the other hand, volatile-char interactions during the gasification appeared to enhance the Cl retention and prevent the formation of organic chlorine compounds in chars.